Children’s Moral Development in Nigeria: The Parents, the Teachers and the Church (British Journal of Multidisciplinary and Advanced Studies, 2022)
Good moral development is desirable to parents, teachers, the church and the society at large for social, economic, political and technological development in Nigeria. Improper moral development leads to behavioural problems which may be worrisome to the society. This paper therefore examined the basic issues of moral development in children in the context of Nigerian society. First it delved into the meanings of morality and moral development extending it to the roles parents, teachers and the church play for moral development. Consequences of improper moral development as applicable to Nigerian society were highlighted. Conclusions were made on what should be done to inculcate morality in children and adolescents in order to transform Nigerian society for better.
Keywords: Mature morality; immoral; amoral; virtues; integrity; corruption